Microsatellite based DNA fingerprinting of 28 local rice (Oryza sativa L.) varieties of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
A total of 28 local rice (Oryza sativa L.) varieties of Bangladesh were selected for DNA fingerprinting with seven microsatellite DNA markers. Upon PCR amplification the alleles were separated on Agarose gel using a sequencing gel electrophoresis system. The loci were polymorphic (P95) in all of the varieties. Variation was found in number of alleles, allele frequency, observed and expected heterozygosity. The primer, RM335 having motif (CTT)20 also yielded highest number of alleles (15) and highest PIC value (0.909). Genetic differentiation (Fst) values were found in the ranges 0.84 to 1.00 with an average of 0.92 and gene flow (Nm) values ranged from 0.047 to 0.00 with an average of 0.02. High level genetic differentiation and low level gene flow values in 28 rice (Oryza sativa L.) varieties which were indicated of diversity among the varieties as most of these varieties were of landraces. Over all Nei’s genetic distance value (D) ranged from nil to 2.56 among 378 varietals pairs resulting as a means of permutation combination of 28 rice varieties. The UPGMA dendrograme based on Nei's genetic distance placed the varieties into different clusters. All of the varieties were identified with at least one and/or combination of 7 primers. Keywords: Microsatellites; DNA fingerprinting; Oryza sativa; Bangladesh DOI: 10.3329/jbau.v8i1.6391J. Bangladesh Agril. Univ. 8(1): 7-17, 2010